ANALISIS GRAFIS GERAKAN SENDI TERHADAP POROS VERTIKAL TULANG BELAKANG PENARI BAPANG MALANGAN - Teguh Sasmito; Gatot Soebiyakto; Nurida Finahari (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2021)
Injuries in dancing activities can occur while practicing or during performance. Repetitive movements can be a major cause of injury when dancing. One of the injuries that can be fatal is spinal cord injury. The clinical manifestations of injury to the spine arise based on the location of the trauma. This study aims to identify potential movements that can cause spinal cord injury from the Bapang Malangan Dance. This potential is viewed from the movements that have a rotational effect on the spinal cord. The research was conducted by imitating several dance movements that were considered to have the potential to cause rotational motion in the spine. The measurement results of the spine rotational angle are used as the basis for carrying out kinematic and dynamic analysis. The degree of potential injury arising from movement is referred to at the normal allowable angle. From the results of the study, it is known that the area of ​​the neck segment from the spinal line of Bapang Malangan dancers is a potentially injury critical area. This is related to the rotation angle that occurs (50-60o) exceeds the maximum limit of normal rotation (45o). The load that works at the point of rotation is the weight of the head which act as pendulum with a combination of compressive effects. The development of research can be directed to the dynamic effects of dance movements, focusing on the study of modes of motion 2 that produce rotational changes in the entire spinal line, studying the combined effects of other body parts, and considering the dancer's skill.